Longitudinal Raman Spectroscopic Observation of Skin Biochemical Changes due to Chemotherapeutic Treatment for Breast Cancer in Small Animal Model. (16th July 2017) - Seong, Myeongsu; Myoung, NoSoung; Lee, Songhyun; Jeong, Hyeryun; Yim, Sang-Youp; Kim, Jae Gwan
Abstract : The cancer field effect (CFE) has been highlighted as one of indirect indications for tissue variations that are insensitive to conventional diagnostic techniques. In this research, we had a hypothesis that chemotherapy for breast cancer would affect skin biochemical compositions that would be reflected by Raman spectral changes. We used a fiber-optic probe-based Raman spectroscopy to perform preliminary animal experiments to validate the hypothesis. Firstly, we verified the probing depth of the fiber-optic probe ( 800 μ m) using a simple intravenous fat emulsion-filled phantom having a silicon wafer at the bottom inside a cuvette. Then, we obtained Raman spectra during breast cancer treatment by chemotherapy from a small animal model in longitudinal manner. Our results showed that the treatment causes variations of biochemical compositions in the skin. For further validation, the Raman spectra will have to be collected from more populations and spectra will need to be compared with immunohistochemistry of the breast tissue.